PERANAN ZEOLIT NANOPORI TERMODIFIKASI SEBAGAI MATERIAL PENGONTROL PELEPASAN PUPUK UREA - Hidayat, Rahmat; Fadillah, Ganjar; Chasanah, Uswatul; Wahyuningsih, Sayekti (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Effectiveness of catalyst zeolite nanoporous as a slow release fertilizer of nitrogen from urea has been researched. In this study, natural zeolite was activated by HF 1% with a calsination temperature at 120oC and the surface of zeolite was modified by aminopropyltrimethoxysilane (APTMS) 5%. Zeolite activation was characterized by X-ray diffraction spectroscopy (XRD) and Surface Area Analyzer (SAA) while the modified zeolite was characterized by infrared spectroscopy (FTIR), Surface Area Analyzer (SAA) and UV-Vis spectroscopy. The results of the material characterization of zeolite-APTMS obtained size pore of 7,74 nm with a maximum adsorption capacity of urea was 3.668 mg/g. Slow release urea test from zeolite-APTMS performed by observing the absorbance of the urea at a wavelength of 195 nm with a variation of time 0, 5,10,20,40,60,80,100 and 120 minutes The test of fertilizers in the soil is directly done by observing changes pH and release of NH4+ in the incubation time of 14 days. The results show that urea without zeolite will be released 100% in the 120 minute and zeolite-APTMS aqueous solution at minute 120 only released about 56,24%. While the application of fertilizers in the soil is directly obtained that urea with zeolite having a pH decrease slowly compared to urea without zeolite. It is addressed that the zeolite-APTMS potentially be developed as a release control material of nitrogen from urea is caused due to the ability of the zeolite to absorb urea-APTMS temporarily in the pore and hydrogen bonding interactions between the urea and N-H from APTMS. Keywords: zeolite, zeolite-APTMS, urea, slow release fertilizer